Perbandingan System Economic Order Quantity dan Sistem Just In Time: terhadap Efisiensi Biaya Bahan Baku pada PT. Tricitra Agri Perdana - Simanjuntak, Desy Juliana; Sidharta, Juaniva; Josephine, Suzanna (Universitas Kristen Indonesia, 2017)
This study aims to compare the Economic Order Quantity and Just In Time in determining the efficiency of raw material cost, and determine which method is best to apply to PT. Tricitra Agri Perdana when viewed from the efficiency of raw material cost. Analytical tools used in this research are the methods of EOQ and JIT. Data obtained from the interviews with staff who deals with the purchase of raw materials, and storage supplies at PT. Tricitra Agri Prime. The research results showed that PT. Tricitra Agri Prime could depress spending or expenses at the company so that the company's costs haven't really run well due to JIT methods still provide supplies of raw materials.Keywords: system economic order quantity and just in time, perbandingan EOQ dan JIT.